The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/ntr/ntt046
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Opioid Detoxification: Behavioral Changes and Response to Treatment

Abstract: The relevance of tobacco use in opioid addiction (OA) has generated a demand for available and more effective interventions. Thus, further analysis of less explored nicotine-opioid clinical interactions is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 66 publications
5
31
0
Order By: Relevance
“…This difference was not present among baseline smokers. This result is consistent with the literature suggesting better drug abstinence outcomes (or proxies of outcomes) in non-smokers or former smokers (Haney et al, 2013; Mannelli et al, 2013; Peters et al, 2012; Winhusen et al, 2014), but demonstrates this relationship in a large, geographically diverse outpatient SUD (non-opioid) adult population. This relationship appears to be robust, and it may be possible that reducing smoking early in the SUD treatment may serve to improve treatment response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This difference was not present among baseline smokers. This result is consistent with the literature suggesting better drug abstinence outcomes (or proxies of outcomes) in non-smokers or former smokers (Haney et al, 2013; Mannelli et al, 2013; Peters et al, 2012; Winhusen et al, 2014), but demonstrates this relationship in a large, geographically diverse outpatient SUD (non-opioid) adult population. This relationship appears to be robust, and it may be possible that reducing smoking early in the SUD treatment may serve to improve treatment response.…”
Section: Discussionsupporting
confidence: 91%
“…Among users of both tobacco and cannabis, a recent review showed poorer cannabis cessation outcomes compared to cannabis only users (Peters, Budney, & Carroll, 2012), and a human laboratory-based study showed that co-users of tobacco and cannabis were more likely to relapse (to cannabis) compared to non-smoking cannabis users (Haney et al, 2013). Smoking during opioid detoxification was shown to increase opioid craving (Mannelli, Wu, Peindl, & Gorelick, 2013). It has also been found that cocaine-dependent patients who stopped smoking in response to smoking cessation treatment provided concurrently with SUD treatment had improved cocaine-use outcomes relative to those who continued to smoke (Winhusen, Kropp, Theobald, & Lewis, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that the majority of people who ceased opioids (60% in AAs and 66% in EAs) also ceased cocaine is consistent with evidence of high rates of co-occurrence of OUD and cocaine use disorder (CUD) (39,40), which supports the development of treatment strategies to target both disorders (39,41), and suggests that ceasing one substance might influence, or reflect, the ability to cease the other. Our findings are also consistent with observations that failure to address tobacco use lowers the efficacy of opioid cessation treatment (42) and that a behavioral intervention in patients with antisocial personality disorder reduces substance use (43). Unlike problems that are associated with other drug use, which predicts lower odds of opioid cessation, we found having cannabis use related problems predicts higher odds of opioid cessation (i.e had two marijuana symptoms lasting a month; marijuana interferes with work).…”
Section: Discussionsupporting
confidence: 89%
“…Smoking is associated with more severe SUD symptoms (Mannelli, Wu, Peindl, & Gorelick, 2013), worse SUD treatment outcomes (Frosch, Shoptaw, Nahom, & Jarvik, 2000; Peters, Budney, & Carroll, 2012), and increased mortality among those with SUDs. Of particular concern, smoking may be a stronger contributor to mortality in this population than other substance use (Hurt et al, 1996; Lanier, Johnson, Rolfs, Friedrichs, & Grey, 2012).…”
Section: Introductionmentioning
confidence: 99%